Available phosphorus levels for 95 to 120 kg barrows genetically selected for lean gain - Arouca, Cláudio Luís Corrêa; Silva, Francisco Carlos de Oliveira; Fontes, Dalton de Oliveira; Donzele, Juarez Lopes; Oliveira, Rita Flávia Miranda de; Haese, Douglas; Kill, João Luís; Paula, Eriane de (Revista Brasileira de Zootecnia, 2011)
With the objective of evaluating available phosphorus (aP) levels in diets for barrows selected for lean meat deposition, eighty commercial hybrid pigs with initial weight of 94.05±1.05 kg were used in this experiment. Pigs were allotted in a completely randomized block design, with five treatments (0.092, 0.156, 0.220, 0,284, and 0.348% of aP), eight replicates and two pigs per experimental unit. The average daily weight gain of pigs increased and the feed conversion improved quadratically with increasing aP in the diets up to the estimated levels of 0.21 and 0.20%, respectively. There was no effect of the dietary aP on average daily feed intake. However, aP intake, bone strength and concentration of phosphorus in the bones increased linearly with increasing aP in the diets. The levels of aP did not affect carcass traits; however, the alkaline phosphatase activity was improved and the values of serum inorganic phosphorus increased quadratically up to the estimated levels of 0.26 and 0.27% of aP, respectively. The available phosphorus levels of 0.21, 0.27, and 0.35%, corresponding to daily aP intakes of 6.34, 8.13, and 10.44 g result, respectively, in greatest performance, blood and bone parameters of 95 to 120 kg barrows selected for lean gain.
Keywords: Carcass; Finishing; Minerals; Nutrition; Performance